1994
DOI: 10.1289/ehp.94102s1091
|View full text |Cite
|
Sign up to set email alerts
|

Fluoromicroscopic studies of bleomycin-induced intracellular oxidation in alveolar macrophages and its inhibition by taurine.

Abstract: The mechanism of bleomycin-induced pulmonary fibrosis is not yet clear. Recent studies have shown that alveolar macrophages (AM) can be stimulated by bleomycin in vitro releasing inflammatory cytokines, suggesting that the interaction of bleomycin with AM is an important step in the drug-induced fibrotic process. Bleomycin is known to bind DNA and generate oxygen radicals through complexation with Fe2+ and oxygen. To provide more insight into the cellular oxidative property of bleomycin, we have developed a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Thus, it is shown here for the first time in isolated Kupffer cells that taurine, at physiologically attainable concentrations, significantly blunted LPS-induced elevations in [Ca 2ϩ ] i and that this process is most likely linked to the observed reduction in TNF-␣ production. Taurine, at concentrations used here, also blocked the bleomycin-induced increase in [Ca 2ϩ ] i in isolated alveolar macrophages [42]. However, it did not prevent TNF-␣ production completely, most likely because Kupffer cells contain receptor-mediated pathways (i.e., scavenger receptor) that, although dependent on calcium [7], may not be affected by taurine.…”
Section: Taurine Prevents the Increase In [Ca 2ϩ ] I Due To Lps In Kumentioning
confidence: 66%
“…Thus, it is shown here for the first time in isolated Kupffer cells that taurine, at physiologically attainable concentrations, significantly blunted LPS-induced elevations in [Ca 2ϩ ] i and that this process is most likely linked to the observed reduction in TNF-␣ production. Taurine, at concentrations used here, also blocked the bleomycin-induced increase in [Ca 2ϩ ] i in isolated alveolar macrophages [42]. However, it did not prevent TNF-␣ production completely, most likely because Kupffer cells contain receptor-mediated pathways (i.e., scavenger receptor) that, although dependent on calcium [7], may not be affected by taurine.…”
Section: Taurine Prevents the Increase In [Ca 2ϩ ] I Due To Lps In Kumentioning
confidence: 66%
“…Another in vitro study showed that BLM induces a substantial rise in intracellular calcium and a significant generation of intracellular reactive oxygen species in rat AM (Bhat et al, 1994). These studies suggest that intracellular oxidative events in AM may play an important role in BLM-mediated inflammatory lung injury.…”
Section: Discussionmentioning
confidence: 88%
“…This BLM-induced apoptosis, lung inflammation, and fibrosis can be significantly attenuated by treatment with a caspase inhibitor (Kuwano et al, 2001). In a previous study, it was demonstrated that BLM induced intracellular oxidation in AM, and this action was accompanied by a rise in intracellular calcium levels (Bhat et al, 1994). Both reactive oxygen species and intracellular calcium are known to alter mitochondrial functions (Green & Reed, 1998), suggesting that BLM may produce apoptosis through a mitochondrial pathway.…”
Section: Time-dependent Apoptosis Of Alveolar Macrophages From Ratsmentioning
confidence: 91%